Charitable giving: Framing and the role of information - Claudia Keser; Maximilian Späth (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2021)
We study the impact of information on the effectiveness of a taking frame in the context of charitable giving. In our laboratory experiment, either the decision maker (giving frame) or the recipient (taking frame) receives an endowment. In both cases, the decision maker can freely decide the final allocation of the money. In addition to the frame, we vary the level of information that we provide about the worthiness of the receiving charity. In keeping with our theoretical prediction, participants donate significantly more, when the decision is framed as taking rather than as giving. However, this framing effect is smaller, the more information we provide on the charity.
Keywords: C91; D64; D80; 330; Information; Giving; Taking; Charity; Experiment